A preliminary study on the freezing tolerance of milkfish (Chanos chanos, Forskal) embryos. - Buendia, Jeremiah C.
Milkfish embryos of blatula and C-shape stages were tested for cryoprotectant toxicity using DMSO and glycerol at 10, 12 and 15 concentrations. Survival and hatching as well as the effects of freezing were observed. Glycerol was more toxic than DMSO. Freezing at 4 degrees centigrade resulted in the decrease of hatching, and ice crystal formation killed the embryos during the process of freezing to 80 degrees centigrade. C-shaped embryos had a higher survival and hatching than the blastula stage embryos in the toxicity and cold shock tests.